2007
DOI: 10.1016/j.yexcr.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion by VAMP3 and plasma membrane t-SNAREs

Abstract: Pairing of SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins on vesicles (v-SNAREs) and SNARE proteins on target membranes (t-SNAREs) mediates intracellular membrane fusion. VAMP3/cellubrevin is a v-SNARE that resides in recycling endosomes and endosome-derived transport vesicles. VAMP3 has been implicated in recycling of transferrin receptors, secretion of α-granules in platelets, and membrane trafficking during cell migration. Using a cell fusion assay, we examined membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 53 publications
3
33
0
Order By: Relevance
“…The exclusive presence of 80 kDa SNARE complex in the capacitated cavitated membrane fraction supports the possibility of SNARE-mediated docking and priming of PM and OAM. A role of the syntaxin 1B/SNAP 23/VAMP 3 complex in the regulation of exocytosis has been reported for other cell types [25]. Moreover, the conformational switch of a specific syntaxin isoform (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…The exclusive presence of 80 kDa SNARE complex in the capacitated cavitated membrane fraction supports the possibility of SNARE-mediated docking and priming of PM and OAM. A role of the syntaxin 1B/SNAP 23/VAMP 3 complex in the regulation of exocytosis has been reported for other cell types [25]. Moreover, the conformational switch of a specific syntaxin isoform (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple readout systems have been developed to detect fusion of the cells that express flipped v-SNAREs (v-cells) and the cells that express flipped t-SNARE proteins (t-cells) Hu et al, 2003;Hu et al, 2007). In the microscopic assay shown in Fig.…”
Section: Microscopic Cell Fusion Assaymentioning
confidence: 99%
“…There are putative N-glycosylation motifs (Asn-X-Ser/Thr) in VAMPs. Our previous studies (Hu et al, 2003;Hu et al, 2007) showed that N-glycosylation disrupts the function of flipped SNAREs, and that treatment of tunicamycin, an antibiotic that inhibits N-glycosylation (Elbein, 1984), restores the fusion activities of flipped SNAREs. To prevent N-glycosylation of VAMPs 1, 4, 5, 7 and 8, v-cells expressing these VAMP proteins and control cells are incubated in cell culture medium containing 10 g/ml of tunicamycin during transfection.…”
Section: Enzymatic Cell Fusion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the cell surface receptors depleted is the Transferrin Receptor (TfR), the prototypical recycling protein, which cycles between the PM and the early and recycling endosome compartments [5]. We demonstrated that the reduction in TfR levels on the cell surface is not due to degradation, as total cellular levels of TfR are unaltered during infection, and that injection of EspG results in the movement of the TfR to cytosolic vesicles positive for markers of recycling endosomes [4], [6], [7]. Therefore, we hypothesize that EspG may inhibit the recycling of internalized cell surface receptors back to the PM.…”
Section: Introductionmentioning
confidence: 95%